2020
DOI: 10.1021/acsestwater.0c00186
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Bisphenol AF during Aqueous Chlorination: Kinetics, Mechanisms, and Influence of pH

Abstract: In this study, the reaction kinetics and degradation mechanism of bisphenol AF (BPAF) with hypochlorous acid (HOCl) were investigated for the first time. Our results showed that BPAF could be effectively degraded by chlorine over a wide pH range from 5.3 to 11.7, with apparent second-order rate constants (k app) of 1.0–175.5 M–1 s–1 at temperature 25 ± 1.8 °C. By kinetic modeling, k app of un-ionized and ionized BPAF (i.e., BPAF, BPAF–, and BPAF2–) were calculated to be 2.9 ± 1.1, (9.0 ± 0.4) × 103, and (1.4 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…S19 and S46df) or a mutual-activation degradation (Fig. S47) [41]. Moreover, electrochemical amperometric i-T curves of CTd-S2 showed a negative and concentration-dependent current jump after addition of free chlorine and reasserted the reduction of free chlorine by the foreign electron of CTd-S2 (see discussions of Fig.…”
Section: Resultsmentioning
confidence: 87%
“…S19 and S46df) or a mutual-activation degradation (Fig. S47) [41]. Moreover, electrochemical amperometric i-T curves of CTd-S2 showed a negative and concentration-dependent current jump after addition of free chlorine and reasserted the reduction of free chlorine by the foreign electron of CTd-S2 (see discussions of Fig.…”
Section: Resultsmentioning
confidence: 87%
“…The coupling reactions between phenolic compounds catalyzed by enzymes or metals have been reported. , Phenoxyl radical generation via a single electron transfer was found to be a critical intermediate for the coupling reactions. ,, Similarly, in this study, chlorine oxidation induced electron transfer from acetaminophen, resulting in the formation of acetaminophen radicals. The formed acetaminophen radicals could further react via three pathways: (1) an additional electron transfer to form NAPQI; (2) self-bonding to form self-coupling products; and (3) addition to the benzene ring of acetaminophen to form dimer radicals.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have also confirmed that dermal absorption can contribute to exposure to BPA [20,21] through contact with thermal paper in which BPA is added as a printing developer [22], and especially after the use of skin and hand sanitizers containing dermal penetration enhancing chemicals [23]. Interestingly, water disinfection methods can aid in the removal of BPA from drinking water [24][25][26][27].…”
Section: Introductionmentioning
confidence: 97%